Legal Review of Umpire's Decision in England vs New Zealand Cricket Final - Ade Putra Hasibuan; Vikas Kumar Chaudhary (Indonesian Journal of Sports Law, 2025)
Abstract Cricket is a game played by 2 (two) antagonistic teams that can be played by anyone, both young and old. Cricket means a game that is almost similar to softball and baseball. Cricket does not mean an individual game but a team game. Each team consists of 11 people so that there is cooperation between players to produce victory. Cricket is a sport that originated in England, cricket has been very popular in British colonies such as India, Pakistan, Australia, Malaysia and others. For those who are new to cricket, this sport uses a bat, stump, ball and field. However for matches such as the final, there must be an additional match so that the rules of international matches need to be changed. What are the Cricket rules that should be changed and considered to neutralize the laws, which currently tend towards batsman? The ICC should do something about the bails. During IPL as well as the World Cup, so many times we have seen that bails are not falling despite ball hit the stumps. It should not be like that. In an event like the world cup, it happened 5 times so far in the first ten days. Nothing can be more frustrating for a bowler than this. There are a few things that I think can resolve this issue. Keywords: Cricket, Umpire’s Decision, International Cricket Council